Microhardness of the enamel exposed to whitening dentifrices - Arruda, Alex Mendez de [UNESP]; Briso, André Luiz Fraga [UNESP]; Oliveira Júnior, Osmir Batista de [UNESP]; Santos, Paulo Henrique dos [UNESP]; Tosti, Simone Cristina [UNESP] (My University, 2012)
The purpose of this study is to verify the effect of three different types of dentifrices on the superficial microhardness of bovine enamel. Methods: Forty-eight 4x4mm dental fragments were polished and randomly divided into 4 groups: GI, conventional silica-based dentifrice; GII, hydrogen peroxide-based dentifrice; GIII, carbamide peroxide-based dentifrice; and GIV, immersion in artificial saliva. After polished, the specimens received five indentations of 25g static load, for 5 seconds. Subsequently, specimens from groups GI, GII and GIII were immersed in solution containing dentifrice and distilled water, in weight proportion of 1:2, for 15 minutes daily. After this period, fragments were rinsed in tap water and stored in artificial saliva at 37oC. This procedure was repeated for 21 days and then a new analysis of the microhardness was performed. Results and conclusion: The results were submitted to ANOVA and Fisher’s test at 5%. It was concluded that all samples treated with dentifrices showed hardness decrease, being most pronounced in dentifrices containing peroxide.

O objetivo deste estudo é verificar o efeito de dentifrícios à base de peróxido de carbamida, peróxido de hidrogênio e um convencional rico em sílica, na microdureza superficial do esmalte bovino. Métodos: Para tanto, 48 fragmentos dentais de 4 x 4mm foram polidos, realizada então a leitura inicial da microdureza, e divididos aleatoriamente em 4 grupos: GI - dentifrício convencional; GII - dentifrício contendo peróxido de hidrogênio; GIII - dentifrício contendo peróxido de carbamida e GIV - imersão em saliva artificial. Após o polimento, os espécimes receberam 5 indentações de carga estática de 25 gramas, por 5s. Após essa fase, os espécimes dos grupos GI, GII e GIII foram imersos em suspensão contendo dentifrício e água destilada, na proporção de 1:2 em peso, durante 15 minutos diários. Decorrido este período, os fragmentos foram lavados com água corrente e armazenados em saliva artificial a 37oC. Esse tratamento foi repetido por 21 dias e, após esse período, foi realizada a análise final da microdureza. Resultados e conclusão: Os resultados foram submetidos aos testes estatísticos ANOVA e teste de Fisher a 5%. Concluiu-se que todas as amostras tratadas com dentifrícios sofreram diminuição na dureza, sendo esta mais pronunciada nos dentifrícios contendo peróxido.
Análise da microdureza em esmalte bovino exposto a dentifrícios clareadores
Keywords: Dentifrices; Dental enamel; Peroxides; Dentifrícios; Esmalte dentário; Peróxidos